Effect of Counseling Using Flipcharts and Video Media on Increasing Adolescent Reproductive Health Knowledge at Senior High School 1 Muara Pahu - Elysa Sriwidiastuti; Jasmawati Jasmawati; Indah Nur Imamah (Rifa'Institute, 2023)
Introduction: The low knowledge of adolescents about reproductive health causes increasingly complex problems. Efforts to prevent deviant behavior such as premarital sex in adolescents need to be given in the hope that it will influence changing their behavior so that adolescent health knowledge can increase. Objective: To determine the effect of counseling using flipcharts and video media on increasing adolescent reproductive health knowledge at SHS 1 Muara Pahu. Methods: The research design in this study was quantitative using a quasi-experimental design. The research was carried out in February-April 2022. The sample was determined using Simple Random Sampling, so the research sample consisted of 72 respondents. The statistical test used is Paired Simple T-Test if it is obtained t count (p-value) < 0.05, then the hypothesis Ha is accepted and Ho is rejected. Result and Discussion: There is a difference in the increase in knowledge of adolescent reproductive health before and after being given counseling using flipcharts and video media (pValue = 0.00). Conclusion: There is an effect of counseling using flipcharts and video media on increasing adolescent reproductive health knowledge at SHS 1 Muara Pahu.